(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Objective: the purpose of this study was to compare the technical efficiency of Italian hospitals at a regional level and to examine if differences could be explained by organisational and contextual factors. Technical efficiency was defined as the ability of the operating units evaluated to use optimal resource levels for their level of output. Methods: the effect of external factors was explored through a second stage Data Envelopment Analysis (DEA). Efficiency scores were calculated for each hospital using the DEA method (Stage I). Through Tobit regression analysis, the estimated efficiency scores were regressed against a set of organisational and contextual characteristics beyond managerial control, which reflected differences in the population demographics and regional health expenditure (Stage II). Stage I and Stage II efficiency scores were compared in order to indirectly assess managerial contribution in relation to hospital efficiency. Results: the highest efficiency (M±SD) was observed in hospitals in the North-West (75.7±15.1), followed by those in the North-East (75.5±15.1), Central Italy (73.9±16.4) and then Southern Italy (70.6±17.9). Hospital Trusts (HTs) were shown to be more technically efficient than Local Public Hospitals (LPHs). Organisational and contextual indicators were statistically significantly different at Tobit regression analysis for HTs and LPHs. Emilia Romagna and Lombardia were the regions whose management contributed to increased efficiency. Conclusions: in our study, the distribution of regions according to technical efficiency only partly reflected the North-South gradient shown by other studies regarding the gap of expenditure. The important role of organisation and environment in establishing efficiency differences among hospitals was demonstrated.